The Aesthetics of the Built Environment: A Post-Kantian Look at Bioregionalism and Ecomimicry Approach in Environmental Design - Dimitry Ratulangie Ichwan (STF Driyarkara - Diskursus, 2022)
Kant regarded ecosphere as having the highest degree of beauty, as opposed to other aesthetical objects such as painting, sculpture, buildings, and we could infer, the built environment. His arguments hinges heavily on his transcendental philosophy, where he stressed that pure beauty could only be achieved through disinterested judgement, without concept, and others. Though his proposition for ecosphere is valid, it could not be used to justify other cases, such as determining the degree of beauty of the built environment. Thus, a modified version of Kant's aesthetics needs to be adopted, as it opens space for the built environment. This research uses Kant's overarching aesthetical arguments to justify the degree of beauty of the built environment. It is found that the built environment could have similar, if not same to, the degree of beauty of ecosphere by way of bioregionalism and ecomimicry, where the totality of the built environment encompases the natural law of local environment, making its degree of beauty as high as ecosphere. Abstrak Kant memandang tinggi atas lingkungan alam dan menobatkannya sebagai derajat keindahan tertinggi bila dibandingkan dengan objek estetis lainnya seperti lukisan, patung, gedung, dan kita dapat inferensikan, lingkungan buatan manusia. Argumen dia terjangkar kepada pemikiran transendentalnya, di mana keindahan murni hanya dapat didapatkan melalui penilaian tanpa ketertarikan, tanpa konsep, dan lain-lain. Walaupun proposisinya terhadap lingkungan alam valid, kita tidak dapat menggunakannya untuk menjustifikasi derajat keindahan lingkungan buatan manusia. Dengan itu, sebuah modifikasi dari pemikiran Kant diperlukan untuk dapat menilai lingkungan buatan manusia. Penelitian ini menggunakan teori estetika Kant untuk menjustifikasi derajat keindahan lingkungan buatan alam. Dipertahankan bahwa lingkungan buatan manusia memiliki derajat keindahan yang sangat mendekati, bahkan sama, dengan lingkungan buatan alam jika, dan hanya jika, lingkungan buatan tersebut mengadopsi konsep bioregionalisme dan ecomimicry, di mana totalitas dari lingkungan buatan manusia mencakupi hukum alam yang terdapat di daerah lokal, meningkatkan derajat keindahan lingkungan buatan tersebut.